English Language Creativity and Academic Achievement A Study of Gender and Locality Differences - Tyagi, Tarun Kumar; Kumar, Manish; Gupta, Pragya (JOURNAL OF INDIAN EDUCATION, 2022)
The main aim of the present study was to investigate the gender and locality differences of English Language Creativity of senior secondary students. As a by-product of the main study, the relationship between English Language Creativity, Academic Achievement, and English Language Achievement was also examined. Sixty-seven eleventh grade students from three schools of Gaya District, India, age range from 16–19 years were included in the sample by using the convenience sampling technique. English Language Creativity test developed by Malhotra and Kumari (1990) was administered to the students. Academic achievement and English language achievement were measured based on grade/percentage of marks obtained by the students in their previous examination. Mann-Whitney U test and Kendall Rank correlation (τ) were used to analyse the data. The results revealed that gender and locality differences were found in English language creativity, i.e., female students were found better than their counterparts on dialogue writing and poetic diction whereas urban students were found better than their counterparts. Furthermore, gender and locality differences were also found in the dimension of language creativity except for flexibility. Subsequently, it is also revealed that English language creativity was found to be positively related to academic achievement and English language achievement. Plausible explanations and implications of the findings of the research are discussed.